Cognitive and neural strategies during control of the anterior cingulate cortex by fMRI neurofeedback in patients with schizophrenia - Cordes, Julia S.; Mathiak, Krystyna A.; Dyck, Miriam; Alawi, Eliza M.; Gaber, Tilman J.; Zepf, Florian D.; Klasen, Martin; Zvyagintsev, Mikhail; Gur, Ruben C.; Mathiak, Klaus (Frontiers in Behavioral Neuroscience, 2015)
Cognitive functioning is impaired in patients with schizophrenia, leading to significant disabilities in everyday functioning. Its improvement is an important treatment target. Neurofeedback (NF) seems a promising method to address the neural dysfunctions underlying those cognitive impairments. The anterior cingulate cortex (ACC), a central hub for cognitive processing, is one of the dysfunctional brain regions in schizophrenia. Here we conducted NF training based on real-time functional magnetic resonance imaging (fMRI) in patients with schizophrenia to enable them to control their ACC activity. Training was performed over three days in a group of 11 patients with schizophrenia and 11 healthy controls. Social feedback was provided in accordance with the evoked activity in the selected region of interest (ROI). Neural and cognitive strategies were examined off-line. Both groups learned to control the activity of their ACC but used different neural strategies: Patients activated the dorsal and healthy controls the rostral subdivision. Patients mainly used imagination of music to elicit activity and the control group imagination of sports. However, the difference in neural control did not result from the differences in cognitive strategies but from diagnosis alone. Based on social reinforcers, schizophrenia patients can learn to regulate localized brain activity. Cognitive strategies and neural network location differ, however, from healthy controls. These data emphasize that for therapeutic interventions in schizophrenia compensatory strategies may emerge. Specific cognitive skills or specific dysfunctional networks should be addressed to train impaired skills. Social neurofeedback based on fMRI may be one method to accomplish precise learning targets.